Multiple Attribute Decision Making Menggunakan Metode TOPSIS Dalam Penentuan Staff Marketing Terbaik - Setiawansyah Setiawansyah; Very Hendra Saputra; Sanriomi Sintaro; Ahmad Ari Aldino (Graha Mitra Edukasi, 2023)
Multiple Attribute Decision Making (MADM) is an approach used in decision making to select the best alternative from a number of given criteria or attributes. This research aims to apply the TOPSIS method in selecting the best marketing staff so that it can become a reference and benchmark for companies in selecting the best marketing staff using a decision support system model. The results of the ranking of the selection of the best marketing staff who got rank 1 with a value of 0.644, namely Ahmad, rank 2 with a value of 0.539, namely Hermawan, rank 3 with a value of 0.529, namely Santoso, rank 4 with a value of 0.443, namely Jayanti, rank 5 with a value of 0.399, namely Heru.